Journey of Journal of Forensic Medicine & Toxicology and way forwards - Gupta, Sanjay (Journal of Forensic Medicine and Toxicology, 2025)
Dear Readers and Friends,I am deeply saddened by the sudden demise of Prof.O.P. Murty, a stalwart in the Forensic fraternity. His contributions to the field and JFMT are immeasurable, and his legacy will be remembered forever.As a token of respect, we have proposed an award in his name to the Indian Academy of Forensic Medicine (IAFM) to recognize his tireless efforts and academic contributions. In 2022, the Journal of Forensic Medicine and Toxicology (JFMT) was facing many turbulences in its existence. I was entrusted with the responsibility of reviving it, and I, along with my team, worked tirelessly to restore its reputation. Our efforts paid off at a significant personal and professional cost. We incurred monetary losses, sacrificed opportunities, and devoted countless hours to develop the domain and coping with immense stress.Today, JFMT stands as one of the premier national journals in Forensic Medicine and Toxicology, a testament to our unwavering dedication and hard work.As I complete the tenure of three years as Editor, I acknowledge the invaluable contributions of our team.